Design and Evaluation of a Physical Protection System for a Radioactive Waste Intermediary Storage - Victor de Castro Vasconcelos; Gladson Silva Fontes; Renato Luiz Tavares (Brazilian Journal of Radiation Sciences, 2022)
The present work aimed to describe, present, and evaluate a Physical Protection System (PPS) for a hypothetical facility of an intermediate radioactive waste deposit, following international and national security criteria. Therefore, it carried out an evaluation of the Physical Protection System (PPS) applying the DEPO (Design and Evaluation Process Outline) methodology with a sequence of three phases of the protection system design and assessment of its vulnerabilities. The overall assessment of PPS was performed from the calculation of the overall probability of system effectiveness (PE) through the methods of adversary sequence diagrams, path analysis, and neutralization analysis. PPS presented a PE value of only 6.5%, three improvements were proposed and their impacts were analyzed. The reduction of the response time of the security forces led to a value of 78% of the PE and the increase of the time delay (TD) in the barriers closer to the target made the PPS efficiency reach 92%, higher than the acceptable value of 85%. The results showed that the evaluation of the proposed hypothetical project allowed adaptations so that the ideal level of PPS effectiveness could be reached with few interventions. The initial project was prepared in accordance with current regulations (traditional prescriptive approach) and, even so, presented a low probability of overall effectiveness, leading to the need for adjustments that were only possible by applying the DEPO methodology (performance-based approach).